A general method to determine the optimal whitecapping dissipation coefficient in the SWAN model - Lei, Zhifeng; Wu, Wenfan; Gu, Yanzhen; Zhai, Fangguo; Li, Peiliang (Frontiers in Marine Science, 2023)
Whitecapping dissipation is a critical term in affecting the accuracy of wave height modeling. However, the whitecapping dissipation coefficient (Cds), as a primary factor influencing whitecapping, is commonly determined through trial and error in various studies. In this study, we present a general method for calibrating the Simulating Waves Nearshore (SWAN) wave model using the whitecapping dissipation term, demonstrated through a detailed study in the South China Sea (SCS). Theoretical analysis reveals that the optimal Cds value shows a one-to-one correspondence with the applied wind field. Expectedly, under high-quality wind field conditions, the optimal Cds values tend to fall within a narrow range, regardless of the model domain or time span. Numerical experiments executed in the SCS further consolidated this inference, encompassing two common wind input schemes (ST6 and YAN) and three distinct whitecapping dissipation schemes (KOMEN, JANSSEN, and WST). Based on the experimental results, we have identified an optimal Cds range for each whitecapping dissipation scheme. Cds values within the optimal range consistently outperformed the default Cds in the SWAN model. Subsequent experiments verified the method’s applicability to the Gulf of Mexico and the Mediterranean Sea. The findings suggest that this research holds substantial promise for practical applications on a global scale.